Humanist Ideals in an Era of Increasing Confrontation: The Need to Renew Basic Paradigms - Vitulyova, Yelizaveta; Gabrielyan, Oleg; Bakirov, Akhat; Suleimenov, Ibragim (Journal of Ecohumanism, 2024)
The nature of qualitative transformations of warfare at the present stage is analyzed. It is shown that these transformations will inevitably lead to the question of partial transfer of individual’s intelligence to non-biological information carrier. In particular, in the foreseeable future it is predicted that AI will emerge based on the intelligence of officers who possess advisory combat experience. It is shown that tasks of this kind can be solved by existing software tools. It is also shown that the solution of the problem of partial transfer of an individual’s consciousness to a non-biological information carrier goes beyond the concept of transhumanism in its existing version. AI built on such a basis, regardless of its intended purpose, becomes a kind of an intermediary between a person and the suprapersonal level of information processing. It is shown that the emergence of such intermediaries can significantly affect social relations, in particular, significantly increase the influence of those philosophical concepts that insist on the importance of collectivism as a factor that is closely related to the humanistic picture of the world. It is shown that, paradoxically, the development of military AI will inevitably serve as one of the factors giving a new impetus to the ideals of humanism.